Age differentiation of americans as a factor of the english language lexical system development - Wieler, G. O.; Dmyterko, Y. V.; Вілер, Ганна Олександрівна; Дмитерко, Євгенія Володимирівна (My University, 2022)
The article deals with social aspects of lexical innovations in modern English. Age differentiation of Americans is analyzed through the prism of their influence on the development of the lexical system of the English language. Neologisms which denote different age groups are put in the spotlight of socio-linguistic research. В статті розглядаються соціальні аспекти лексичних інновацій сучасної англійської мови. Вікова диференціація американців представників американського суспільства розглядається крізь призму її впливу на розвиток лексичної системи англійської мови. Неологізми на позначення різних вікових груп представлено в світлі соціолінгвістичного дослідження.
Вікова диференціація американців як фактор розвитку лексичної системи сучасної англійської мови
Wieler G. O. - ORCHID: 0000-0002-5042-1220; Dmyterko Y. V. - ORCHID:0000-0002-0530-2249.
Keywords: neologisms; age differentiation; lexical system; socio-linguistics; неологізми; вікова диференціація; лексична система; соціальна лінгвістика